The Implementation of the Think Pair Share (TPS) Learning Model to Improve the Student’s Motivation and Learning Outcomes in the Bioenergy Course - Nur Efendi (Postgraduate, University of Mataram, 2026)
For improving the Bioenergy course learning outcomes, the Think Pair Share (TPS) Learning Model are implementing in this research with qualitative descriptive research methods. The research results show that the average student learning motivation = 3.69 which is also categorizing as good in the implementation, the student's learning outcomes in the Bioenergy course for the individual proportion index (P) for the 28 students = 0.82 ≥ 0.80, and the class proportion index (P) = 1.00 ≥ 0.80, the meaning are that the individual and class completeness have complete and achieve in the good category. From the result research can show that the TPS can make the Bioenergy course easy to understand both conceptually and in terms of application in the life, make the student discussions interesting, increase the learning motivation, and make the students as the center of learning. The learning model like this, it is going to follow up in the various activities and continuously to improve the quality of higher education in our country and nation.